Occurrence and variation of lipophilic shellfish toxins in phytoplankton, shellfish and seawater samples from the aquaculture zone in the Yellow Sea, China. (1st March 2017) - Li, Meihui; Sun, Geng; Qiu, Jiangbing; Li, Aifeng
Abstract: Lipophilic shellfish toxins (LSTs) produced by diverse microalgae have become a potential threat to the marine aquaculture industry in coastal regions throughout the world. In this study, phytoplankton, scallop, and seawater samples were collected and monitored in the aquaculture zone of Liuqing Bay located in the coast of Qingdao, Yellow Sea, in 2014 and 2015. Dissolved LSTs in seawater were adsorbed by solid phase adsorption toxin tracking (SPATT) bags and solid phase extraction (SPE) cartridges, respectively. PTX2 was found to be the predominant LSTs, while OA and DTX1 were detected at trace levels in the three species of Dinophysis and Phalacroma genera picked from the investigation zone. The highest quota of PTX2 occurred in D. fortii (0.28 pg cell −1 ), followed by D. acuminata complex (0.08 pg cell −1 ) and P. rotundatum (= D. rotundata ) (0.02 pg cell −1 ). PTX2 (nd∼5.7 μg kg −1 ), OA (nd∼2.8 μg kg −1 ) and DTX1 (nd∼1.6 μg kg −1 ) were also observed in cultivated scallops, but in addition to the former, PTX2sa, 7- epi -PTX2sa and an isobaric form of DTX1 suspected as DTX1b were also found in the SPATT bags. The isobaric compound of DTX1 only appeared in the SPATT bags deployed in field samples of seawater. A significant higher quantity of OA was adsorbed by SPATT bags compared to DTX1, although similar concentrations of both toxins were adsorbed by SPE cartridges from the aquaculture zone. AZA2 was also found in the concentrated phytoplankton cells, which demonstrated that AZA-producing microalgae were present in this investigated area. The variation in concentrations of PTX2 adsorbed by SPATT bags could reflect the change of Dinophysis density in seawater, but there was a time lag behind the peaks of Dinophysis density. Comparative results did not support the SPATT technology as a useful warning tool for toxic algal blooms and toxin accumulation in bivalves. The data suggest that the contamination of LSTs was prevalent in the coast of Qingdao and the environmental behavior of LSTs should be explored further. Graphical abstract: Highlights: Lipophilic shellfish toxins were monitored in coastal aquaculture zone of Qingdao. Microalgae, scallop, and seawater samples were collected by multiple approaches. Dinophysis acuminata, D. fortii, and Phalacroma rotundatum were identified here. A novel compound isobaric DTX1 was found only in SPATT bags deployed in field. A discrepancy was mentioned for OA and DTX1 adsorbed by the SPATT bags in field.